Lanthanum carbonate for dialysis patients with hyperphosphataemia resistant to sevelamer: A retrospective cohort study - Asrar Khan; Titi Chen; Anis Khan; Elaine Chan; Karen Byth; Jackson Tan; David Harris (Cogent Medicine, 2016)
Introduction: Lanthanum carbonate (LC) and sevelamer hydrochloride (SH) are non-calcium-based phosphate binders (NCPB), used to manage hyperphosphatemia in patients with chronic kidney disease. We compared the efficacy of LC and SH in lowering serum phosphate level in patients on haemodialysis or continuous ambulatory peritoneal dialysis. Methods: Treatment profiles of a group of dialysis patients on NCPB were retrospectively analyzed between 2010 and 2014 for a mean duration of one year. The treatment group included patients (n = 28) who were initially on SH and switched to LC because of uncontrolled hyperphosphataemia. Patients receiving ≥12 months SH treatment were included in the control group (n = 10). Results: There was a significant within patient fall in serum phosphate from a mean of 2.4 ± 0.5 mmol/L after 3–6 months on SH to 1.7 ± 0.4 mmol/L following 3–6 months on LC (p < 0.001). These within patient changes differed significantly from those observed in the control group (interaction p = 0.003). Mean phosphate binder pill burden also fell significantly from 5.6 ± 2.3 tablets to 2.6 ± 0.8 tablets daily (p < 0.001). A significant within patient increase in serum bicarbonate level from 23.2 ± 3.5 to 24.7 ± 2.7 mmol/L (p = 0.020) was observed in the treated patients, reflecting a resolution of mild acidosis associated with the hydrochloride salt of sevelamer which was not evident in the control group (interaction p = 0.022). Conclusion: This study demonstrates the efficacy of LC in reducing the serum phosphate level, pill burden, and improving bicarbonate level in dialysis patients.